Penerapan Strategi Pemasaran Pedagang Bakso di Laut Dendang Jatian Gang Bunga Kecamatan Medan Tembung Percut Sei Tuan - Zainarti Zainarti; Soibatul Aslamia Nasution; Aida Lasmi; Ella Sri Wahyuni Ningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research is motivated by the problem of the income of the meatball traders in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan District, which has started to decline compared to the previous year due to a decrease in visitors, this has happened since the last year. This meatball seller in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan sub-district, has actually implemented a marketing strategy but has not had a major impact on the level of family welfare. The aims of this study were: To find out the marketing strategies that have been applied by meatball traders in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan District in improving family welfare, To find out what marketing strategies are dominant and used by meatball traders in Laut Dendang Jatian Gang Bunga, District Medan Tembung Percut Sei Tuan in improving family welfare, To find out the impact of implementing a trader's marketing strategy in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan District on increasing family welfare. The type of research conducted by the author is field research. This study emphasizes qualitative methods, which explain the Marketing Strategy of Meatball Traders in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan District in Improving Family Welfare. This research method uses a quantitative description of the data obtained, namely data in the form of interviews, observations and documentation and then explains it in the form of descriptions of words not in the form of numbers which are then presented in the form of analytical reports. The results of this study indicate that, 1) The marketing strategy carried out by meatball traders in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan sub-district, is a strategy of product, price, place, promotion like Kotler's theory where in a business must apply these 4 marketing theories. 2) The dominant marketing strategy used by meatball traders in Poncol District, Magetan Regency, is product strategy, although they apply the 4 marketing strategies according to Kotler, the dominant strategy is product strategy. 3) The impact of the marketing strategy on the level of welfare of the family of meatball traders in Laut Dendang Jatian Gang Bunga, Medan Tembung Percut Sei Tuan District, is at the stage I prosperous family level according to Ms. Siti, namely families who have been able to meet their basic needs at a minimum, but have not been able to meet all of their needs. psychological social. Kata Kunci : Marketing Strategy, Family Welfare